Geographical Analysis of the Displacement: Asylum Seekers of Syrian in Kilis - Incili, Omer Faruk; Akdemir, Ilhan Oguz (Marmara Univ, 2016)
About 10 million people were displaced as a result of internal conflict that took place in Syria in 2011. Today, about 3 million of them (2,743,497) are spread throughout 81 districts of Turkey. Located on the most major migration route of migrants, Kilis underwent some changes due to the stress caused by this rapidly increasing population. The population which is twice its own population hosted by Kilis is what makes it significant in terms of Syrian asylum seekers. Another element that renders the study field substantial is the location of Kilis on the crossing route of Syrian asylum seekers spread throughout Turkey. The purpose of this study is to set forth the origin of migration in this forced migration process and the demographic characteristics of those joining the migration. In addition, this study reveals how the targeted Kilis is affected by this forced migration. With the study, the results of questionnaire performed by the participation of 300 Syrian asylum seekers were revealed. While the half of the population among interviewees lives in the city center, the other half is comprised of those residing in Elbeyli Besiriye and Oncupinar container settlements. For the purposes of the study, the findings were handled by the reductive approach. In addition, some predictions were made regarding future cases through the progressive method. There are some theories that motivates the migration process. For example, the existence of those acquaintances or relatives of asylum seekers in Kilis prior to migration may be described through the network theory.
Keywords: Geography; migration; Syria; asylum seekers; refugees; Kilis